Indirect Household Determinants of Child Nutrition: A Literature Review on Parenting, Health Access, Food Security - Zulfa erianti; Kasmita kasmita; Yuliana Yuliana; Anisa Amalia; Indah Muthia Ayuni; Ramadhanti Ramadhanti; Anni Faridah (Jurnal Berkala Kesehatan, 2026)
Infants are children aged 0–59 months who are in a phase of rapid growth and development, making them highly vulnerable to nutritional disorders. National data shows that in 2018 there was an increase in the prevalence of very short toddlers (11.5%) compared to the previous year (9.8%), although the prevalence of short toddlers remained relatively stagnant (19.3% in 2018 and 19.8% in 2017). This condition indicates that chronic nutritional problems are still a public health challenge in Indonesia. One factor contributing to growth disorders is inadequate nutritional intake in children, which in the household context is closely related to parenting patterns and feeding practices by mothers. These factors are categorized as indirect causes, which include parenting patterns, access to health and social services, household food security, and family eating habits. This study aims to identify and analyze indirect determinants that affect children's nutritional status at the household level. The study uses a Systematic Literature Review (SLR) approach to ten indexed national articles that have undergone peer review, published between 2015 and 2025. The included articles focused on children under five years of age in Indonesia, examined indirect determinants of nutritional status, and used quantitative or mixed research designs. Data synthesis was conducted through thematic content analysis to identify patterns of relationships between indirect determinants and children's nutritional status. The results of the study showed that indirect determinants had a significant influence on children's nutritional status through complex and interrelated mechanisms. Inadequate parenting patterns, low household food security, limited maternal education, suboptimal use of health services, poor sanitation, and unbalanced family eating habits contribute to an increased risk of infection, inadequate nutrient intake, and stunted growth in children. These factors do not work independently but influence each other in determining the risk of infection and nutritional status in children.